Assessment of 39K, 232Th, and 238U isotopes in soil samples with ICP-MS in El-Obied, Sudan (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The main objective of the present study was to determine the concentrations of the radioisotopes potassium-39K, thorium-232Th, and uranium-238U in soil samples collected from selected areas around El-Obeid City, Sudan. Inductively Coupled Plasma Mass Spectroscopy (ICP-MS) analysis was employed to quantify these isotopes. Soil samples were obtained from five locations surrounding El-Obeid, specifically from two regions in the southern and western parts of the city within North Kordofan State, in areas located away from residential zones. High correlation coefficients between 232Th and 238U indicate that these isotopes likely originate from the same source. Principal component and factor analyses further confirm that 232Th and 238U share common sources in the soil samples collected from various locations around El-Obeid City. In addition, the measured concentrations of 238U and 39K are in reasonable agreement with values reported in the literature. The concentration of 232Th observed in this study is relatively high compared to values reported from other regions worldwide, suggesting possible local geological or anthropogenic influences.